Paradoxes of professional regulation : in search of regulatory principles - Trebilcock, M. J. (University of Toronto Press, 2022)
"Occupational licensure, including regulation of the professions, dates back to the medieval period. While the guilds that performed this regulatory function have long since vanished, professional regulation continues to this day. For instance, in the United States, 22 percent of American workers must hold licenses simply to do their jobs. While long-established professions have more settled regulatory paradigms, Paradoxes of Professional Regulation presents a case for stronger regulation of other professions, taking note of incompetent services and the serious risks they pose to the physical, mental, or emotional health, financial well-being, or legal status of uninformed consumers. Michael J. Trebilcock examines five case studies of the regulation of diverse professions, including alternative medicine, mental health care provision, financial planning, immigration consultants, and legal services. Noting the widely divergent approaches to the regulation of the same professions across different jurisdictions - paradoxes of professional regulation - the book is an attempt to develop a set of regulatory principles for the future. In its comparative approach, Paradoxes of Professional Regulation gets at the heart of the tensions influencing the regulatory landscape, and works toward practical lessons for bringing greater coherence to the way in which professions are regulated."--